Distinct Nutrient Sources and Infant Outcomes: Impact of Breastmilk and Complementary Food on Indonesian Infant Growth and Micronutrient Status - Sofa Rahmannia; Kevin Murray; Gina Arena; Aly Diana; Siobhan Hickling (Proceedings)
The relationship between infant nutrient intake and their nutritional status remains uncertain [...]